Konsep Ketuhanan Agama Agama, Toleransi Dan Pluralisme Agama - Sriyono Fauzi; Aulia Arsinta; Ikke Fitriana Nugrahini (4, 2024)
In the era of increasingly widespread globalization, intercultural interactions and religious diversity have become inevitable realities in the social dynamics of world society. This paper examines three main concepts, namely divinity, religious tolerance, and religious pluralism, and their application in the context of increasingly complex religious diversity. The concept of divinity in various religions reflects a panorama of diverse views of the Divine, from monotheism in Islam, Christianity and Judaism, to polytheism in Hinduism. Religious tolerance, which reflects an attitude of respect for diversity of beliefs, faces various challenges such as religious extremism and prejudice. Religious pluralism, which emphasizes the value and truth of various beliefs, is important in interreligious dialogue and interfaith cooperation. Through literature-based qualitative research, this paper identifies strategies to promote tolerance and respect for diversity of beliefs, as well as overcome barriers to realizing an inclusive and harmonious society. The research results show that a deep understanding of different concepts of divinity, promotion of religious tolerance, and respect for religious pluralism are key to building a peaceful and diverse global society. Abstrak Pada era globalisasi yang semakin meluas, interaksi antarbudaya dan keberagaman agama telah menjadi realitas yang tak terelakkan dalam dinamika sosial masyarakat dunia. Makalah ini mengkaji tiga konsep utama, yaitu ketuhanan, toleransi agama, dan pluralisme agama, serta implikasinya dalam konteks keberagaman agama yang semakin kompleks. Konsep ketuhanan dalam berbagai agama mencerminkan panorama keberagaman pandangan akan yang Ilahi, dari monoteisme dalam Islam, Kristen, dan Yahudi, hingga politeisme dalam Hinduisme. Toleransi agama, yang mencerminkan sikap menghargai keberagaman keyakinan, menghadapi berbagai tantangan seperti ekstremisme agama dan prasangka. Pluralisme agama, yang menekankan nilai dan kebenaran berbagai keyakinan, penting dalam dialog antaragama dan kerjasama lintas agama. Melalui penelitian kualitatif berbasis literatur, makalah ini mengidentifikasi strategi untuk mempromosikan toleransi dan penghargaan terhadap keragaman keyakinan, serta mengatasi hambatan-hambatan dalam mewujudkan masyarakat yang inklusif dan harmonis. Hasil penelitian menunjukkan bahwa pemahaman mendalam tentang perbedaan konsep ketuhanan, promosi toleransi agama, dan penghargaan terhadap pluralisme agama adalah kunci dalam membangun masyarakat global yang damai dan beragam.